Relationship between sources of pet acquisition and euthanasia of cats and dogs in an animal shelter: a pilot study. Issue 6 (June 2017) - Arbe Montoya, AI; Rand, JS; Greer, RM; Alberthsen, C; Vankan, D
Abstract : Objective: Approximately 140, 000 unwanted dogs and cats are culled in Australia annually. There is a paucity of information linking sources of pet acquisition with subsequent euthanasia, which may inform evidence‐based strategies to reduce euthanasia rates. This pilot study aimed to determine whether there is a higher risk of euthanasia related to the source of acquisition for pets surrendered to an animal shelter. Methods: Data for 5391 dogs and 5581 cats surrendered to one Queensland shelter between January 2006 and December 2009 were analysed. Results: The main sources of acquisition for owner‐surrendered dogs were 'shelter' and 'pet shop' and for owner‐surrendered cats were 'own litter' and 'shelter'. Euthanasia rates for different sources varied. For adult dogs, acquisition through newspaper advertisements was associated with the highest euthanasia rate. Adult cats obtained as gifts (from friend or family member) had the highest euthanasia rate. For junior cats, the overwhelming source was the owner's own litter (68% of intake) and only kittens acquired as strays were at significantly higher risk of euthanasia. For both dogs and cats, animals acquired from shelters had lower rates of euthanasia than most other sources, which suggests that shelter‐sourced animals may be considered a preferred source for pet acquisition to assist in reducing the number of adoptable pets euthanased. Conclusion: There was evidence from the study animal shelter that the risk of euthanasia was related to acquisition source. These findings should be confirmed by prospective studies, which should also investigate the interaction between acquisition source and other factors, using larger data sets from a variety of shelters.